Cassazione, Sezione Civile, sentenza no 2487/2017: Court of Cassation, Civil Section, Decision no 2487/2017: Di Palma (President); Cristiano, Acierno, De Marzo, Counsellors; Campanile, Counsellor and Rapporteur: 31 January 2017. (9th December 2017) - Unknown
ABSTRACT: Marriage – Same-sex marriage – Recognition – Two female French citizens, one of whom iure sanguinis also Italian citizen, contracting lawful marriage in France in accordance with French law – Whether Italian public authority required to transcribe marriage in marital status register for civil effects – Whether transcription conflicted with principles of Italian family law – DPR 396/2000, art 19 – L 218/1995, art 28 – ECHR, art 12